Straightforward synthesis of the pentasaccharide repeating unit of the cell wall O-antigen of Escherichia coli O43 strain - Shit, Pradip; Misra, Anup Kumar (Glycoconjugate journal, 2020)
A concise synthetic strategy has been developed for the synthesis of the pentasaccharide repeating unit of the cell wall O -antigen of Escherichia coli O43 strain involving stereoselective β-D-mannosylation and α-L-fucosylation using corresponding trichloroacetimidate intermediates and perchloric acid supported over silica (HClO 4 -SiO 2 ) as glycosylation promoter. The yield and stereoselectivity of the glycosylations were very good.